Lateral Response Comparison of Unbonded Elastomeric Bearings Reinforced with Carbon Fiber Mesh and Steel - Ali Karimzadeh Naghshineh; Ugurhan Akyuz; Alp Caner (Shock and Vibration)
The vertical and horizontal stiffness used in design of bearings have been established in the last few decades. At the meantime, applicability of the theoretical approach developed to estimate vertical stiffness of the fiber-reinforced bearings has been verified in different academic studies. The suitability of conventional horizontal stiffness equation developed for elastomeric material, mainly for steel-reinforced elastomeric bearings, has not been tested in detail for use of fiber-reinforced elastomeric bearings. In this research, lateral response of fiber mesh-reinforced elastomeric bearings has been determined through experimental tests and the results have been compared by corresponding values pertaining to the steel-reinforced bearings. Within the test program, eight pairs of fiber mesh-reinforced bearings and eight pairs of steel-reinforced bearings are subjected to different levels of compressive stress and cyclic shear strains. Fiber-reinforced elastomeric bearings may be more favorable to be used in seismic regions due to lower horizontal stiffness that can result in mitigation of seismic forces for levels of 100% shear strain. Damping properties of these types of fiber mesh-reinforced bearings depend mostly on the selection of elastomeric material compounds. Suggestions have been made for the lateral response of fiber-reinforced elastomeric bearings. It has also been determined that the classical equation for lateral stiffness based on linear elastic behavior assumptions developed for elastomeric bearings does not always apply to the fiber-reinforced ones.